PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL DAN PERTUMBUHAN EKONOMI DAERAH KALIMANTAN BARAT BAGIAN TIMUR - B61109050, GORDIANUS DEDI (Jurnal Ekonomi Daerah (JEDA), 2014)
The research objective was to determine the effect of Local Revenue (PAD), the General Aallocation Fund (DAU), Special Allocation Fund (DAK), and Capital Expenditure on Economic Growth in West Kalimantan Eastern Region, which includes: 1) To assess the effect of PAD to Capital Expenditure; 1) To assess the effect of DAU on Capital Expenditure; 3) To assess the effect of the Capital Expenditure DAK, and, 4) To assess the effect of Capital Expenditures on Economic Growth. Verification study was to verify previous research that has been done. While descriptive studies are used to illustrate the problems associated with the research objectives, collecting data and explain the data obtained in accordance with the requirements. Research using secondary data, the data obtained in the form of ready-made. Budgets and GDP data in the form of West Kalimantan Eastern District from 2005 to 2011 which is the time series data. Answer the purpose of research and analysis carried out to test the following hypotheses: 1) Description of the development of local revenues, capital expenditures, and GDP in 2005-2011; 2) To see the strength of the relationship between government revenue and capital expenditure economic growth, correlation analysis was used.; And 3) The effect of local revenue to capital spending and economic growth, were analyzed using regression tools. Based on this research, the effect of PAD to significant capital expenditure a statistically significant 95% of data support the hypothesis. DAU influence on capital expenditure a statistically significant 95% of data support the hypothesis. DAK influence on capital expenditure a statistically significant 95% of data support the hypothesis. Effect of capital expenditure on economic growth is significantly a statistically significant 95% of data does not support the hypothesis. Â Keywords: PAD, DAU, DAK, capital expenditure